A Preliminary Report of the Survey on Teaching Strategies, Phase 1 An Evaluation by Students in the A.B. Political Science Program - Aguja, Hilton J.; Arquisal, Amabelle B.; Castro, Luz C. Sevidal (2010)
This article is based on data templates contained in the report of the Department of Political Science of the College of Arts and Social Sciences for the college research forum, "Report on the Highlights of the Survey on Teaching Methods and Strategies". The data templates were culled from a study of students' evaluation of the effectiveness of teaching methods and strategies. The study refers, in general, to students' perspectives about the methods employed in the foundation courses at the College of Arts and Social Sciences, as well as, those used in the major courses of the respective students' programs. Phase 1, the initial phase of this study, was a survey in 2007 among seniors/graduating students (as of first semester and second semester of School Year 2006-2007) conducted simultaneously in six (6) degree programs of the CASS.

The main basis for this write-up consists of the mean scores that had been computed from the results of the aforementioned survey in which the graduating students of the Department of Political Science were respondents. In that survey, the graduating students rated the techniques employed in the subjects (foundation courses and major courses) that they had taken at the College of Arts and Social Sciences. These techniques had been grouped into clusters of methods for Skills, Learning Activities, Resource Materials, and Evaluation.

A synopsis of this report was presented by Professor Darwin J. Manubag at the College Rescuch Forum, "Report on the Highlights of the Survey on Teaching Methods and Strategies," held on 9 Aug 2010 at the CASS Bulwagang Filipino, College of Arts and Social Sciences.
Keywords: Political science -- Study and teaching; Curriculum evaluation